THE ROLE OF THE PHYSICIAN IN THE MANAGEMENT OF STROKE: PATHOPHYSIOLOGY, DIAGNOSIS AND CURRENT THERAPEUTIC APPROACHES (International Seven Journal of Health Research, 2025)
It is hoped that this article can facilitate the understanding of stroke management, as well as clarify doubts on the subject. The general objective of this study is to understand the role of the physician in the management of stroke, its pathophysiology, how the diagnosis should be made, and the necessary therapeutic approaches. The aim is to provide a comprehensive and practical view for application in the clinical context.